Pedestrian reported activity and information preference while waiting at a red light - Meng Liu; Xiangling Zhuang; Changxu Wu; Guojie Ma (IET Intelligent Transport Systems)
Abstract The development of pedestrian signal lights made it a promising information center to distribute information to assist safe road crossing and provide “controlled engagement” to improve waiting experience. To determine what types of information to display, this study surveyed 555 pedestrians on frequency of their existing activities while waiting at a red light and preference of several types of information based on results of a structured interview. Pedestrian reported 14 types of activities, from which the four categories with decreasing frequency were extracted based on factor analysis: scene perception, recreation, mental activity, and anxiety activity. The participants reported more mental and anxiety activity have higher need for external displayed information on signal lights. Overall, among the four information categories extracted from 24 specific information types with factor analysis, pedestrians preferred road crossing and contextual information the most, with less preference on learning and appreciation information. The least preferred information is entertainment information, within which they even disliked entertainment news and general commercial ads ( vs. local ones). There are also individual differences in preference for these information categories. The findings have implications on information design for the roadside signal lights as well as advanced traveller information system in general.